Guaraníes misioneros” reexaminados. Acerca del discutido papel de los curas y la religión en la conflictividad política latinoamericana (fines del siglo XVIII y principios del XIX) - María Elena Barral (Nuevo mundo - Mundos Nuevos, 2009)
This article sheds light on two major contributions to the study of the Guarani under the Missions –both published in 2009. These are Guillermo Wilde’s Religión y poder en las misiones guaraníes, andLía Quarleri’s Rebelión y guerra en las fronteras del Plata, Guaraníes, jesuitas e imperios coloniales. These publications underscore indigenous agency and deemphasize the role of the Jesuits. This change in the focus –from the Jesuits to the indigenous people and their leaders– connects these contributions to the more or less recent scholarship which has studied social conflicts where religion and ecclesiastics acted differently –for instance, in Mexican insurgency. Our analysis of these two books underlines indigenous agency and religion, how these two issues legitimated indigenous authorities, and how these leaders managed the religious life within this environment. In addition, this article links these contributions to the historiography of the Mexican insurgency given that both had to review long-standing views on the role of religion and the ecclesiastics in shaping peasant protest.